Elasticity - Theory, Applications, and Numerics (2nd Edition) - Sadd, Martin H (Elsevier, 2009)
Elasticity is concerned with determining the strength and load carrying ability of engineering structures including buildings, bridges, cars, planes, and thousands of machine parts that most of us never see. It is especially important in the fields of mechanical, civil, aeronautical and materials engineering. This book provides a concise and organized presentation and development of the theory of elasticity, moving from solution methodologies, formulations and strategies into applications of contemporary interest, including fracture mechanics, anisotropic/composite materials, micromechanics and computational methods. Developed as a text for a one or two-semester graduate elasticity course, this new Second Edition is the only elasticity text to provide coverage in the new area of non-homogenous, or graded, material behavior. End of chapter exercises throughout the book are fully incorporated with the use of MATLAB software.